Le fratture di polso e la lesione di Galeazzi - Vicenti, G.; Abate, A.; Carrozzo, M.; Colella, A.; Moretti, B. (Lo Scalpello - Journal, 2018)
DISTAL RADIUS AND GALEAZZI FRACTURES Fractures of the distal radius are the most common fractures in children and adolescents, accounting for 40% of all fractures. Distal radius fractures occur most frequently during early adolescence. The mechanism of injury is usually a fall on a hyperextended wrist. Fractures of the distal radius usually involve the metaphysis. Although physeal (growth plate) injuries are relatively rare, they must be considered carefully because they can result in premature growth arrest. Shortening of the radius can lead to ulnar impaction and triangular fibrocartilage complex (TFCC) tears. The two most common types of distal radial metaphyseal fractures are torus fractures and greenstick fractures. A complete fracture passes through both cortices of the distal metaphysis (distal third) of the radius and/or ulna, often with displacement. A Galeazzi fracture is a fracture of the distal third of the radius along with dislocation of the distal radioulnar joint or ulnar physeal separation (Galeazzi-equivalent fracture). This article reviews current concepts regarding distal forearm fractures in children and adolescents, with particular attention to classification, recommended treatment options and long term complications.